Comparative performance analysis of wireless RSSI in wireless sensor networks motes in tropical mixed-crop precision farm - Azizi, Harun; Ramli, M. F.; Latifah Munirah, Kamarudin; Ndzi, David Lorater; Ali Yeon, Md Shakaff, Prof. Dr.; Ammar, Zakaria; Mahmad, Nor Jaafar (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org